Genetic Parameters of Rice Strains (Oryza sativa L.) Functional for Development and Increasing Production in Medium Plain Dry Lands - Amilia Qurota A'yun; M. Taufik Fauzi; Suwardji; A. A. K. Sudharmawan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Functional rice is a food that contains more than one forming component that is useful for health. Nowadays public interest in functional food is increasing, so functional rice production needs to be increased. Therefore, this research was conducted with the hope of obtaining information on superior agronomic characters to increase the yield power of functional rice strains. The method used was experimental using a randomized group design (RAK). Data analysis consists of Analysis of Variance, genetic diversity coefficient, phenotype diversity coefficient, genotype correlation, phenotype correlation, and heritability in a broad sense. The results showed that the heritability value of high area meaning is found in the character of flowering, harvest age, plant height, panicle length of the amount of grain contained, and the amount of empty grain. The high value of the KKG and KKF is indicated by the character of the number of non-productive saplings, while the lowest value is indicated by the character of the age of harvest. All quantitative characters observed showed positive genotypic correlation results to grain weight per clump. While in phenotypic correlation only the character of plant height, panicle length, the amount of grain containing, the amount of hollow grain and the weight of 100 grains are positive. Based on the analysis that has been carried out the character of plant height, panicle length, the amount of grain containing the amount of hollow grain and the weight of 100 grains need to be taken into account as selection criteria to obtain high-yielding functional rice.